Pengembangan Pemahaman Nilai Sosial Anak Usia Dini melalui Membaca Nyaring Buku Dongeng Toki si Kelinci Bertopi Karya Tere Liye - Subur Subur; Mufliha Mufliha; Heru Kurniawan; Musyafa Ali (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2022)
Reading the loud fairy tale book Toki the Rabbit In Hats by Tere Liye can be done in an effort to develop an understanding of social value for early childhood. This happens because in fairy tales there is always a fun and educational aspect in the development of children's social values. For that, reading the loud fairy tale book Toki the Rabbit Hat by Tere Liye can be done for the purpose of developing an understanding of the social value of early childhood. From there, this research focuses its goal on developing an understanding of social value through proper loud reading activities. The results of the study found that the accuracy of reading aloud toki the Rabbit's Fairy Tale by Tere Liye can be done by paying attention to things: loud and precise pronunciation and pronunciation in reciting sentences that contain social value for early childhood; proper emphasis on the pronunciation of sentences that directly contain social value for early childhood; use appropriate and varied intonation when reciting sentences that contain social value for early childhood; read aloud in a clear and varied voice when reading sentences that contain social values for early childhood; Loud reading is done expressively when reading sentences that contain social values. In this way, the activity of reading the aloud of toki the rabbit's fairy tale book by Tere Liye can be done as a way to develop the social value of early childhood.